Early environment effects on rat photic evoked potentials: A preliminary study - Edwards, H. P.; Barry, W. F.; Spianski, J. O. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This study was designed as a preliminary investigation of the effects of differential early environments on the photic evoked cortical potentials of the albino rat, recorded from the scalp of unanesthetized subjects.